2022
DOI: 10.1155/2022/9282154
|View full text |Cite
|
Sign up to set email alerts
|

Morus alba L. for Blood Sugar Management: A Systematic Review and Meta-Analysis

Abstract: Introduction. Morus alba L. is used for blood sugar management in patients with diabetes mellitus. This review aimed to evaluate the effect of Morus alba on blood sugar management. Methods. This review was conducted in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P). We searched PubMed, EMBASE, and four Korean medical databases (RISS, OASIS, NDSL, and KISS) using relevant keywords. Randomized controlled trials with any type of control intervention were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Chinese herbal Morus alba L. is gaining more attention due to its benefcial medical efects in treating diabetes mellitus (DM) [4,5]. Its extracts and active components have many positive biological efects such as inhibition of alphaglucosidase, antioxidant efect, neuroprotective activity, and anticancer properties [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Chinese herbal Morus alba L. is gaining more attention due to its benefcial medical efects in treating diabetes mellitus (DM) [4,5]. Its extracts and active components have many positive biological efects such as inhibition of alphaglucosidase, antioxidant efect, neuroprotective activity, and anticancer properties [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Mulberry leaves are traditionally used in Asian subcontinent to lower postprandial blood sugar levels 8,9 . Several clinical studies have shown the positive benefit of mulberry leaf extracts on postprandial sugar spikes in healthy as well as diabetic individuals [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Morus alba L. (mulberry) has been used in traditional medicine to treat hyperglycemia, hypertension, dyslipidemia, and diabetes [ 25 - 27 ]. Many researchers have confirmed that M. alba contains various active ingredients, such as polyphenols, flavonoids, anthocyanins, and polysaccharides, which lower lipid levels while also regulating blood sugar levels and antioxidant and anti-inflammatory activities [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%